Rāingān Kānsammanā Sātsanā kap Thōt Prahān Chīwit, 15-16 Karakkadākhom 2551, Samnakngān Khana Kammakān Sitthi Manutsayachon hǣng Chāt (Samākhom Sitthi Sērīphāp khō̜ng Prachāchon, 2008)
Conference on religious perspectives on death penalty.